Facile Synthesis of PVP-Coated Silver Nanoparticles and Evaluation of Their Physicochemical, Antimicrobial and Toxic Activity - Neto, Francisco N. Souza [UNESP]; Morais, Leonardo A. [UNESP]; Gorup, Luiz F.; Ribeiro, Lucas S.; Martins, Tassia J.; Hosida, Thayse Y. [UNESP]; Francatto, Patricia; Barbosa, Debora B. [UNESP]; Camargo, Emerson R.; Delbem, Alberto C. B. [UNESP] (MDPI, 2023)
This study focuses on the synthesis of silver nanoparticles (AgNPs) at different high concentrations and investigates their physicochemical properties, antimicrobial activity, and cytotoxicity. AgNPs were synthesized using the alcohol reduction process, involving the reduction of AgNO3 and its subsequent stabilization via PVP at 80 °C for 4 h. The AgNO3/PVP molar ratio and the average molecular weight were modified in this study. Characterization analyses revealed that the synthesized AgNPs exhibited characteristic surface plasmon resonance absorption peaks at approximately 415 nm, as observed in the UV–Vis spectrum. The results presented in X-ray diffractograms confirmed the face-centered cubic structure of metallic Ag in the nanoparticles. The nanoparticles demonstrated uniform size and shape, with controllable dimensions ranging from 3 to 800 nm. Regarding antimicrobial activity, the MIC solutions exhibited higher potency against the planktonic cells of Candida albicans. The determination of inhibition halos indicated that the silver nanoparticles had an impact on the microorganisms Streptococcus mutans, Candida albicans, and Actinomyces israelii. Furthermore, lower-concentration compositions showed reduced cytotoxic effects compared to higher-concentration particles. Based on the findings, it was concluded that the AgNO3/PVP molar ratio plays a crucial role in the production of AgNPs. These synthesized nanoparticles exhibit desirable physicochemical properties and demonstrate potential antimicrobial activity and controlled cytotoxicity.
Keywords: alcohol reduction process; antimicrobial properties; Ostwald ripening; silver nanoparticles; size control